Relationship between self-care and comprehensive understanding of heart failure and its signs and symptoms. (August 2018) - Lee, Kyoung Suk; Moser, Debra K; Dracup, Kathleen
Background: Although incomplete understanding of heart failure and its signs and symptoms appears to be a barrier to successful self-care, there are few studies examining the relationship between self-care and levels of comprehensive understanding of heart failure and its signs and symptoms. Aim: To determine whether incomplete understanding of heart failure and its signs and symptoms is associated with self-care in heart failure patients who were recently discharged from the hospital due to heart failure exacerbation. Methods: Patients completed the nine-item European Heart Failure Self-care Behavior scale and questionnaire to assess knowledge of heart failure and its signs and symptoms. Three groups were formed by their different levels of understanding of heart failure and its signs and symptoms. Multivariable linear regression was used to determine whether these three levels of understanding groups predicted self-care after controlling for demographic and clinical variables. Results: Of 571 patients 22.1%, 40.1% and 37.8% had poor, moderate, and complete understanding, respectively. Compared with patients in the poor understanding group, patients in complete and moderate understanding groups were more likely to have better adherence to self-care activities (standardized β = −0.14, 95% confidence interval −3.41, −0.47; standardized β = −0.19, 95% confidence interval −4.26, −1.23, respectively). Conclusions: Fewer than half of the patients had a comprehensive understanding of heart failure and its signs and symptoms, which was associated with poor self-care. Our study suggests that patient education should include contents to promote comprehensive understanding of heart failure and its symptoms, as well as the importance of self-care behaviors.